Interpreting Avicenna: Science and Philosophy in Medieval Islam : Proceedings of the Second Conference of the Avicenna Study Group - McGinnis, Jon, (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
This volume provides twelve essays on various aspects of Avicenna's philosophical and scientific contributions, approaching these topics from philological, historical and philosohical methodologies. The work is conceptually divided into four sections: (1) methodology, (2) natural philosophy and the exact sciences, (3) theology and metaphysics and (4) Avicenna's heritage. The First section provides considerations for distinguishing genuine from pseudo Avicennan works. The second section deals with topics encountered in Avicenna's physics, psychology, mathematics and medical theories. The third section treats issues ranging from the theological sources for Avicenna's proof for the existence of God and God's knowledge of particulars to the place of puzzles in Avicenna's Metaphysics as well as the relation of form and matter in Avicenna's thought. The final section considers Avicenna's historical influence on later thinkers such as al-Ghazali as well as his subsequent influence in Persia.